Effect of Inquiry Creative Process Learning Models on Improving the Critical Thinking Ability of Prospective Science Teachers - Ni Nyoman Sri Putu Verawati; Wahyudi Wahyudi; Syahrial Ayub; Wiwin Putriawati; Saiful Prayogi (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Critical thinking has become a very important part as one of the goals of learning at the level of higher education in Indonesia and globally, and learning based on inquiry activities is recommended as a teaching foundation for training learners' critical thinking ability. Teaching inventions towards critical thinking must be trained to prospective teacher for better education in the future. This study aims to determine the effect of the Inquiry Creative Learning (ICP) learning model on improving the critical thinking ability of prospective science teachers. This research is an experimental study with the design of "one group pretest-posttest design". The subject of implementation as a research sample were 20 prospective science teacher who is currently studying at the Faculty of Teacher Training and Education (FKIP), Mataram University, Indonesia. The data of critical thinking ability were analyzed descriptively and statistically, in which homogeneity test, normality test, and t-test were conducted. The results showed that the ICP learning model had an effect on improving critical thinking ability of prospective science teachers.